Characteristics of T- and B-lymphocytes of blood at different stages of pregnancy and peculiarities of immunity in women with preeclampsia - L.E. Tumanova; O.V. Kolomiiets; V.E. Driianska; T.V. Poroshina; O.V. Romaschenko; N.A. Kalinina; O.V. Trokhymovych; A.G. Kornatska; O.P. Ryabenko; O.O. Molchanova (Український Журнал Нефрології та Діалізу, 2023)
The study of immune mechanisms during pregnancy is an important area of research aimed at understanding the immunogenesis of pregnancy and its complications. One such complication is nephropathy, which requires accurate prediction of its course and appropriate therapy.